Elevation of plasma oncostatin M in heart failure. (May 2017) - Gruson, Damien; Ferracin, Benjamin; Ahn, Sylvie A; Rousseau, Michel F
Aim: Oncostatin M (OSM) is an inflammatory cytokine of the gp130 family. OSM could participate in adverse cardiovascular remodeling through regulation of FGF23.Materials & methods: OSM levels were determined in 80 heart failure patients with reduced left ventricular ejection fraction (HFrEF).Results: OSM levels are significantly increased in HFrEF patients compared with healthy subjects. We have also demonstrated that, in HFrEF patients, plasma OSM levels are correlated to parathyroid hormone PTH(1–84) and 1, 25(OH)2 D, two other biomarkers related to bone and mineral metabolism and associated to adverse cardiovascular outcomes.Conclusion: OSM concentrations are elevated in HFrEF patients and could interplay with parathyroid hormone and vitamin D impacting cardiovascular function. Nevertheless, the prognostic value of OSM testing appears limited.